How granularity of data matters in understanding and accelerating racial diversity in U.S. clinical trials. Issue 28 (1st October 2022) - Bebi, Ted; Horovitz, Rachel; Blum, Kevin; Buderi, Robbie; Bourlon, Pierre-Louis; Lamont, Elizabeth W.; Chamberlain, Stephanie; Melhem, Fareed
Abstract : 88 Background: Historically, US clinical trials have been shown to recruit disproportionately large percentages of White patients, raising concerns about the generalizability of clinical trial results to underrepresented racial minority patient populations. Because of this, the FDA has recently reiterated its guidance stating that clinical trials need to reflect the demographic distribution of the US. In this research, we sought to understand how participation of Black patients varies by therapeutic area and geography within the US. Methods: Studying patient-level clinical trial data from an industry-leading historical clinical trial data repository of over 8 million patients from 27, 000 clinical trials, we assessed the racial composition of US interventional trials across indications from 2010 to 2021 which encompassed 433, 822 clinical trial participants across 2, 997 trials. We also analyzed participants' racial composition within the subset of trials from three distinct therapeutic areas (i.e., oncology n = 118, 194, cardiovascular n = 12, 281, central nervous system n = 35, 533) and distinct sites over the same period. Results: The racial distribution of clinical trial participants in the US across all therapeutic areas was 78% White, 15% Black, and 3% Asian. Within the three distinct therapeutic areas, the proportion of Black clinical trial participants varied, with oncology trials reporting 8.5% Black participants, cardiovascular trials reporting 15.3% Black participants, and central nervous system trials reporting 19.9% Black participants. Black participation also varied within a therapeutic area, depending on the indication, as well as by site, with individual sites contributing differently to the racial diversity of trials. Conclusions: Our analysis shows that US interventional trials enroll 15% Black participants, appearing consistent with the 2020 US Census, which estimates that 14.6% of Americans are Black. However, more granular analyses at the level of therapeutic area, indication and site suggest substantial variation in Black participation in clinical trials including a gap in Black representation in oncology trials vs. US Census estimates. This research suggests that aggregate estimates of racial enrollment may mask dramatic variation by other factors like granularity of disease area and geographic location. The study of historic clinical trial data may yield useful insights for accelerating diverse representation in clinical trials.